Impact of type 2 diabetes mellitus on results in the animal naming test in patients with and without liver cirrhosis - Eva Maria Schleicher; Julia Tuchscher; Matthias Weber; Peter Robert Galle; Marcus-Alexander Wörns; Simon Johannes Gairing; Christian Labenz (PLoS ONE, 2025)
Introduction and objectives Diabetes mellitus is a common comorbidity in patients with cirrhosis and is associated with the development of hepatic encephalopathy (HE) and cognitive dysfunction. The simplified Animal Naming Test (S-ANT1) has been established for detecting minimal HE (MHE). It is currently unknown whether S-ANT1 results are affected by diabetes mellitus in patients with and without cirrhosis. Materials and methods This study analyzed data from 268 patients with cirrhosis without signs of HE ≥ 1. MHE was defined using the psychometric hepatic encephalopathy score (PHES). All patients were also tested with S-ANT1. 14 patients with diabetes mellitus and diabetic foot syndrome but no cirrhosis, as well as 37 healthy controls, were also tested with S-ANT1 and served as controls. Results Type 2 diabetes mellitus was present in 79 (29.5%) patients with cirrhosis and MHE according to PHES was detected in 81 (30.2%) patients. In the total cohort, results in S-ANT1 did not differ between patients with and without diabetes mellitus (19 vs. 20 animals, p = 0.108). In multivariable logistic regression analysis, the only variables independently associated with performance in S-ANT1 were PHES-MHE, school education, sodium, and age, while diabetes mellitus was not. Patients with diabetic foot syndrome but no cirrhosis performed poorer in S-ANT1 compared to healthy controls, while patients with cirrhosis and MHE performed poorer than patients with diabetic foot syndrome. Conclusion S-ANT1 seems to be usable for screening for MHE in patients with cirrhosis and type 2 diabetes mellitus, while one might be more cautious when interpreting results in patients with diabetes-related complications.